3D graphene foams/epoxy composites with double-sided binder polyaniline interlayers for maintaining excellent electrical conductivities and mechanical properties. (July 2018) - Wang, Kaili; Wang, Wei; Wang, Haibo; Liu, Liangsen; Xu, Zhiwei; Fu, Hongjun; Zhao, Lihuan; Zhang, Xingxiang; Chen, Lei; Zhao, Yufen
Abstract: Lightweight and easy-processable epoxy composites with high conductivities and mechanical properties were developed by the oxidative polymerization of polyaniline (PANI) coated on porous and freestanding three-dimensional graphene foams (3DGFs). Heat treatment of 3DGFs was prepared, leading to the less defective structure and an increase of conductivity. By surface modification of 3DGFs with PANI (3DGFs-PANI), interface bonding between 3DGFs and epoxy would be strengthened. For epoxy composites with 0.39 wt% 3DGFs-PANI, the conductivity improved almost 12 orders of magnitudes compared with pure epoxy, coming up to 0.036 S/cm. Furthermore, the mechanical tests indicated that epoxy/3DGFs-PANI composites showed higher tensile, flexural and compressive strength. The significant properties of composites aroused from the cooperation of interconnected conductive networks of 3DGFs, conductive PANI interlayers and interfacial bonding between 3DGFs and epoxy. The improved interfacial bonding could be ascribed strong π-π stacking between graphene sheets and PANI, as well as chemical bonding between epoxy and PANI chains.